Intervention - Cook, Robin, 1940- (New York : Berkley Books, 2010)
New York City medical examiner Jack Stapleton considers entering alternative medicine and makes contact with two former college classmates, including an archeologist who is digging beneath Saint Peter's and a bishop who would suppress the archaeologist's findings.
Originally published: New York : G.P. Putnam's Sons, c2009.
Includes bibliographical references (p. [433]).
Keywords: Forensic pathologists -- Fiction; Biotechnology -- Fiction; Alternative medicine -- Fiction; Cancer in children -- Fiction; Bishops -- New York (State) -- New York -- Fiction; Medical novels; Suspense fiction